STUDI FITOKIMIA Baeckea frutescens L: PENGARUH FAKTOR LINGKUNGAN TERHADAP KOMPOSISI KIMIA MINYAK ATSIRI - Tri Murningsih (BERITA BIOLOGI, 2009)
Isolation of two essential oils of Baeckea frutescens L. leaves from different locations (Yogyakarta and Semarang) was done by hydrodistilation. The chemical composition of the oils were analysed by GC-MS. The oils were found to possess chemical compositional differences and considerable variation in the levels of each chemical components, suggesting the existence of chemical varieties.The oils were dominated by monoterpene i.e 8-cineole (22,08-22.67%) and P-pinene (17,98-29.22%).Comparison of chemical composition of the oils analyzed in this study and oils from literatures was conducted to study the effect of environmental factor on the essential oil composition.The result showed that temperature, irradiance, photoperiod and altitute factors influence the chemical composition of essential oils. Tasmanone, a non-terpenic triketone only appears in the essential oils from Quang Binh province (north Vietnam), that have extreme environmental condition.